Fostering positive attitudes towards self-care among the youth in Bongol village during the recovery movement control order - Getrude C. Ah Gang (inScience Press, 2021)
One of the major concerns among the relevant public authorities during the 2019 coronavirus disease (Covid-19) pandemic is the attitude and behavior of the Malaysian society regarding compliance with self-care Covid-19. Although the number of Covid-19 cases is decreasing, public authorities, such as the Malaysian Ministry of Health continually remind people to adhere to the Standard Operating Procedure (SOP) for Covid-19 to reduce the number of cases. To support the authorities’ efforts, a one-day self-care Covid-19 programme involving 10 youths (3 males & 7 females) with a mean age of 17.35 (SD=3.36) was implemented in Bongol village, Tamparuli. To adhere the Covid-19 SOP regulation which prohibits a large number of people from gathering in a confined, crowded and closed spaces, only a few participants were involved. The programme, which was conducted at the Bongol village community hall, involved various organized activities emphasising the three elements of attitude: cognitive, affective, and psychomotor. Before the programme began, all the participants were registered, and their body temperatures scanned to ensure that they were free from any Covid-19 symptoms. Each participant was given a mask and a small bottle of hand sanitiser that could be used throughout the programme. The activities comprised an ice-breaker, a talk on personal self-hygiene, a 20.02-minute self-care video produced by 28 psychology students, personal self-reflections by the participants, a group exercise, a community song, and a two-way discussion on self-care. The Covid-19 self-care programme, implemented with guidance from the Yale Attitude Change Model, emphasizes the practical issue of ‘who says what to whom and with what effects. The participants’ attitude was measured before and after they completed the one-day programme. The results of a Wilcoxon signed-ranked test study showed that there is a significant difference between the participants’ pre- and post-study attitudes towards self-care. The study results showed that the Covid-19 self-care programme, which is based on the social psychology approach, can help foster positive youth attitudes towards self-care. In regard to the authorities’ efforts to lower the number of Covid-19 cases to zero, it is suggested that each party needs (either governmental and non-governmental agencies) to support the Covid-19 campaign and programme by sharing and delivering self-care messages in creative ways to Malaysian communities, especially those in rural areas.